Prevalence and factors associated with smoking in a nationally representative sample of Greek adults: The Hellenic National Nutrition and Health Survey (HNNHS) - George Michas; Emmanuella Magriplis; Renata Micha; Michail Chourdakis; Antonis Koutelidakis; George Dimitriadis; Demosthenes Panagiotakos; Antonis Zampelas (Hellenic Journal of Cardiology, 2022)
Background: The aim of this study was to assess smoking prevalence among Greek adults and in sub-populations with specific sociodemographic and lifestyle determinants. Moreover, to explore the association between smoking and weight status and specific stress-related states. Methods: Data from 3,820 adults (47.5% males), included in the Hellenic National Nutrition and Health Survey, were used. Information was obtained on sociodemographic, lifestyle, anthropometric factors, and stress-related states. Results were obtained using survey-specific analysis. Results: Smoking prevalence was 33.5% in total and was significantly higher in males 39.1% (95%CI: 36.3%–41.8%) compared to females 29.4% (95%CI: 27.4%–31.6%; p < 0.001). Smoking prevalence was higher among those that slept <6 h, consumed daily coffee and alcohol, as well as chronic stress and depressive symptomatology. Moreover, 72.9% of Greek adults were exposed to passive smoke. The odds of having chronic stress, depressive symptomatology, sleep problems, and financial difficulties were higher for current smokers, whereas the odds for overweight/obesity increased only among ex-smokers. Chronic pain was associated with both current and ex-smoking status. Conclusions: This study highlights important sociodemographic and lifestyle factors associated with smoking and underlines associations of ever-smoking with weight status and stress-related states, providing health policymakers valuable information for more effective results.